A whole-of-government review to a whole-of-government response: a narrative review of the United States Government's 2013–2016 West Africa Ebola Epidemic post-operation reports. Issue 6 (18th August 2021) - Rhodes, Megan; Boland, Samuel
ABSTRACT: The 2013–2016 West Africa Ebola Epidemic was and remains the world's largest outbreak of Ebola Virus Disease. The United States Government (USG) spent 2.7 billion responding to the outbreak, predominantly through the deployment of the US Agency for International Development, the Centers for Disease Control and Prevention, and the Department of Defense. Each of these USG agencies, as well as several others, wrote substantive post-operation reports, including myriad recommendations for how to improve interdepartmental coordination and collaboration during future disease outbreak responses. However, to date, no effort has been made to compare and contrast these post-operation reports and their respective recommendations, with a view to finding synergies between them. This essay evaluates the various reports in the public domain, and finds that four areas are consistently referenced: the need to clarify roles and responsibilities between USG agencies, reinforce data sharing and surveillance, perform joint planning, and improve communication and coordination with external partners. These four areas therefore represent high-priority policy interventions for ensuring the efficacy and efficiency of the USG's future interventions in response to critical public health threats.